The Influence of Financial Literacy and Overconfidence on Investment Decisions With Risk Tolerance as A Mediating Variable (A Study on Stock Investors in Bali Province) - Sawitri, Kadek Dewi; Candraningrat, Ica Rika (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Investment decisions are influenced not only by rational calculations but also by psychological biases that affect investor behavior. Grounded in behavioral finance and prospect theory, this study aims to analyze the influence of financial literacy and overconfidence on investment decisions, with risk tolerance as a mediating variable. The research involved 250 stock investors in Bali Province, selected through purposive sampling. Data were collected via structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that financial literacy and overconfidence each have a significant and positive effect on investment decisions. Furthermore, both variables also positively influence risk tolerance, which itself significantly impacts investment decision-making. Risk tolerance mediates the effects of financial literacy and overconfidence on investment decisions, indicating that knowledgeable and confident investors are more willing to take calculated risks aligned with their long-term financial goals. The study contributes theoretically to the development of behavioral finance by confirming the mediating role of risk tolerance in investment behavior. Practically, the findings suggest that financial education and awareness of overconfidence biases are essential in enhancing rational investment behavior. Policymakers and financial institutions are encouraged to develop targeted financial literacy programs and investor profiling tools based on risk tolerance to support more strategic and resilient investment decisions.